2019
DOI: 10.1002/jbio.201900104
|View full text |Cite
|
Sign up to set email alerts
|

Detecting nucleic acid fragments in serum using a magnetically modulated sandwich assay

Abstract: We present a novel assay for rapid and highly sensitive detection of specific nucleic acid fragments in human serum. In a magnetic modulation biosensing (MMB) system, magnetic beads and fluorescently labeled probes are attached to the target analyte and form a "sandwich" complex.An alternating external magnetic field gradient condenses the magnetic beads (and hence the target molecules with the fluorescently labeled probes) to the detection volume and sets them in a periodic motion, in and out of a laser beam.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…The faster turnaround time of the MMB-based assay is achieved by detecting the fluorescence signal at the end of the amplification step (i.e., endpoint detection) rather than monitoring it in real time after each amplification cycle, and by using a much more sensitive optical detection system. The MMB detection system is ∼150 times more sensitive than the direct optical detection system used in a standard RT-qPCR device 20 . Therefore, fewer and shorter amplification cycles are required to reach a detectable level of fluorescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The faster turnaround time of the MMB-based assay is achieved by detecting the fluorescence signal at the end of the amplification step (i.e., endpoint detection) rather than monitoring it in real time after each amplification cycle, and by using a much more sensitive optical detection system. The MMB detection system is ∼150 times more sensitive than the direct optical detection system used in a standard RT-qPCR device 20 . Therefore, fewer and shorter amplification cycles are required to reach a detectable level of fluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…The amplitude of the oscillating signal is proportional to the concentration of the biotinylated fluorescent molecules, which in turn, depends on the initial concentration of the target and the number of amplification cycles (Supplemental Figure S1C). Compared with direct optical detection of the fluorescent molecules, as performed by RT-qPCR, MMB-based detection is ∼150 times more sensitive 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they are laborious and are not useful in point-ofcare settings. Serological tests include the enzyme-linked immunosorbent assay (ELISA) This highly sensitive MMB technology has been demonstrated in several research [11,16] and clinical [16,18,19] applications. For example, the MMB system was used to detect ~0.08 ng/L of the human protein Interluekin-8 (IL-8) in plasma [11], ~100 ng/L of anti-Zika virus IgM and IgG antibodies in serum [16], and fM concentrations of specific DNA sequences [18].…”
Section: Serological Assaysmentioning
confidence: 99%
“…Sensors 2021, 21, x FOR PEER REVIEW 2 of 14 well suited for automation, and improve assay sensitivity, magnetic beads-based assays are commonly used in various bioassays and for biosensing applications [15][16][17][18][19]. Previously, we introduced a novel platform that uses magnetically modulated biosensors (MMB) to rapidly detect very low concentrations of antibodies [20], proteins [21], and specific nucleic acid sequences [22][23][24]. We have shown that the MMB can rapidly identify protein-protein interactions (PPI) in vitro with very high sensitivity [25].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we introduced a novel platform that uses magnetically modulated biosensors (MMB) to rapidly detect very low concentrations of antibodies [ 20 ], proteins [ 21 ], and specific nucleic acid sequences [ 22 , 23 , 24 ]. We have shown that the MMB can rapidly identify protein-protein interactions (PPI) in vitro with very high sensitivity [ 25 ].…”
Section: Introductionmentioning
confidence: 99%